Genetic algorithm optimization of high order surface etched grating tunable laser array - Donegan, John (My University, 2020)
A genetic algorithm is developed with a view to optimizing surface-etched grating tunable lasers over a large optimization space comprised of several variables. Using this approach, a new iteration of slotted lasers arrays are optimized showing significant improvements over previous designs. Output power, lower grating order, fabrication tolerance and performance at high temperatures are among key parameters improved. The new designs feature a much lower grating order (24-29) than used previously (37). The biggest improvement is a near doubling to slope efficiency to 0.1-0.13 mW/mA, with wavelengths from the array covering the C-band . The designs show a reduced sensitivity to etch depth variations. Designs with linewidths down to 100 kHz are also simulated. This algorithm can be readily applied to different wafer materials to efficiently generate slotted lasers designs at new wavelengths.
Keywords: genetic algorithm; surface-etched grating tunable lasers; wafer materials; genetic algorithm; surface-etched grating tunable lasers; wafer materials